Effects of Phaseolus vulgaris Extract on Lipolytic Activity and Differentiation of 3T3-L1 Preadipocytes into Mature Adipocytes: A Strategy to Prevent Obesity - Felipe Castillo; Daniel R. González; Rodrigo Moore-Carrasco (Journal of Nutrition and Metabolism)
Background. Overweight and obesity are defined as abnormal or excessive fat accumulation that may be harmful for health. A global trend in this area is the search for natural compounds that have a proven beneficial effect and no clinical complications. Phaseolus vulgaris (bean) is a vegetable highly consumed worldwide. One of its effects, the most reported, is weight reduction in overweight individuals. Objective. The objective of this study was to investigate the antiobesity activity of this legume in mature 3T3-L1 adipocytes and in rat white adipose tissue in an ex vivo model. Design. Mature adipocytes 3T3-L1 and rat adipose tissue were treated with bean extracts. We quantified lipolysis in mature 3T3-L1 adipocytes and in rat white adipose tissue in an ex vivo model. Results. In an ex vivo assay with adipose tissue, methanolic and aqueous green bean extracts increased glycerol release to the medium compared to control (p<0.05 and p<0.001 respectively). Treatment of 3T3-L1 adipocytes with green bean extracts (800 and 1000 µg/mL) increased glycerol release significantly (p<0.0001). Extracts at concentrations between 500 and 1000 µg/mL reduced intracellular triglyceride accumulation by 34.4% and 47.1% compared to control (p<0.0001). Discussion. Our results propose that bioactive compounds of green beans exert a direct mechanism on adipocytes through lipolysis. Conclusion. We have identified a novel capacity of bean extracts related to lipolytic activity both in vitro and ex vivo, resulting in a powerful lipolytic effect. Moreover, we also found that bean extracts has an antiadipogenic effect during the differentiation of 3T3-L1 preadipocytes. These results suggest that bean is a good candidate for the development of functional ingredients that can help reduce the high rates of death from cardiovascular diseases associated with obesity.